Bleaching Gigi Vital pada Gigi Anterior sampai Premolar Pertama Maksila dan Mandibula (Laporan Kasus) - Melaniwati Melaniwati (Jurnal Kedokteran Gigi Terpadu, 2019)
Background: The discoloration of teeth is a common aesthetic concern for many patients. It can have a profound effect on their self-esteem, interaction with others and employability. Dental bleaching can be used as a treatment for teeth that are discolored due to intrinsic and extrinsic staining. Vital bleaching is an in-office procedure which utilize 25-40% hydrogen peroxides. Home-bleaching with gels containing 10%, 15%, or 20% carbamide peroxide is recommended after in-office procedure. Objective: To overview planning and treatment of vital discoloration teeth with combination in-office and home-bleaching procedure. Case: A 31 year old patient complained about her lack of confidence due to yellow looking teeth. The patient told the dentist she used to consume coffee at least twice a day. Measuring teeth color with Vitapan shade guide (VITA Zahnfabrik) resulted in A3 color for maxillary teeth and A3,5 for mandibular teeth as well as shade guide opalescence results in A3,5 color. The teeth were fully cleaned with brush. Gingiva area was isolated using opaldam, and it was activated using light curing unit  for 10 seconds in each servikal area. Bleaching material was applied to six anterior teeth and first maxillary and mandibular premolar in 20 minutes, it was activated every 5 minute by stirring bleaching material with tip brush. After done with the procedure, bleaching material was cleaned with suction, whipped by using cotton pellet. Color matching was done after in-office bleaching process using Vitapan shade guide (VITA Zahnfabrik), it was attained A1 color for maxillary teeth and A2 for mandibular teeth. Color matching using shade guide opalescence resulted in W3 color. The patient was instructed to use individual tray  through gel containing carbamide peroxide 10% for 8 hours on each day for 1 full week. Conclusion: In-office and home-bleaching procedure is the treatment of choice in vital discoloration of teeth.